2013
DOI: 10.1002/adfm.201302270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Electron Deficient Co‐Monomer on the Optoelectronic Properties and Photovoltaic Performance of Dithienogermole‐based Co‐Polymers

Abstract: particularly successful strategy has been the donor-acceptor approach, in which an electron rich donor is co-polymerized with an electron defi cient acceptor. The co-polymerization has shown to assist the reduction of the band gap by molecular orbital hybridization. [1][2][3][4][5] Computational density functional theory (DFT) calculations on donor-acceptor co-polymers have typically shown that the HOMO is delocalized over the conjugated backbone whilst the LUMO is more strongly localized on the acceptor co-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…[13][14][15] By substituting the bridging carbon atom in PCP-DTBT with Ge, the analogous Ge substituted polymer poly[(4,4′bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]germole)-2,6-diyl-alt-(2,1,3benzothiadiazole)-4,7-diyl] (PGeBTBT, Scheme 1 b) was demonstrated to exhibit a reduced optical band gap. [ 13,14,16,17 ] We also found that the incorporation of the bridging Ge atom resulted in much higher stability to aqueous base than the Si analogue. [ 13 ] This was important because we were able to produce highly purifi ed monomers which afforded high molecular weight polymer by a Suzuki cross-coupling procedure.…”
Section: Introductionmentioning
confidence: 61%
“…[13][14][15] By substituting the bridging carbon atom in PCP-DTBT with Ge, the analogous Ge substituted polymer poly[(4,4′bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]germole)-2,6-diyl-alt-(2,1,3benzothiadiazole)-4,7-diyl] (PGeBTBT, Scheme 1 b) was demonstrated to exhibit a reduced optical band gap. [ 13,14,16,17 ] We also found that the incorporation of the bridging Ge atom resulted in much higher stability to aqueous base than the Si analogue. [ 13 ] This was important because we were able to produce highly purifi ed monomers which afforded high molecular weight polymer by a Suzuki cross-coupling procedure.…”
Section: Introductionmentioning
confidence: 61%
“…4; 21-41). [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] The dithienogermole containing polymers are generally obtained by metal-catalyzed cross-coupling methodologies such as the Stille, Suzuki-Miyaura and Sonogashira reactions, and very high number average molecular weights (M n ) of up to 133000 g mol -1 have been occasionally reported. Due to d-block contraction, 73,74 the electronegativity of germanium is slightly closer to carbon than the related silicon species, 75 therefore reducing the polarization of the Ge-C bond and rendering aryl germanes more tolerable towards bases and nucleophiles than the related aryl silanes.…”
Section: Bulk Heterojunction Solar Cellsmentioning
confidence: 99%
“…32 Compared with their BT counterparts, the PT-containing polymers showed smaller bandgaps and decreased lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy levels. 36 The PT-containing polymer exhibited the smallest bandgap and the largest short-circuit current density (J sc = 19.6 mA/cm 2 ), in comparison with the BTz-containing polymer (J sc = 6.17 mA/cm 2 ) and the ffBT-containing polymer (J sc = 5.74 mA/cm 2 ). In 2013, Heeney and coworkers synthesized three polymers based on benzo[d] [1,2,3]triazole (BTz), 5,6difluorobenzo[c] [1,2,5]thiadiazole (ffBT), and PT, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…32,[36][37][38][39][40][41][42][43] Therefore, it is necessary and meaningful to further investigate the structure-property relationships of PT-containing polymers. However, to the best of our knowledge, none of the reported PCEs of PTcontaining polymers is over 7%, implying that there is still considerable room to improve the photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%